The 7A Framework: Extending the 4A Framework Based on Exchanges in Subsistence Marketplaces in India and Vietnam. (September 2022) - Sarker, Tapan; Dey, Subhendu; Maity, Moutusy; Arli, Denni; Nguyen, Giang
Researchers in the marketing domain have investigated some key drivers of market development in subsistence marketplaces in emerging economies. This article contributes to the literature by proposing a 7A framework that identifies an enhanced set of drivers of market development in subsistence marketplaces in emerging markets (EMs) (by extending the 4A framework). Using qualitative data collected through in-depth interviews with farmers (i.e., micro-entrepreneurs) in subsistence marketplaces from two EMs (countries: India, Vietnam), the study findings provide evidence of the 7A's as facilitators and/or inhibitors of market development in such markets. This article draws attention to the growing importance of the selling processes and strategies used by farmers in such markets for maintaining relationships with customers and investigates the benefits and challenges of selling at farmers' markets that contribute to developing the 7A framework. The study uniquely contributes to the base of pyramid (BoP) literature in emerging markets, which could be of interest to future researchers examining the effectiveness of the 7A marketing framework on micro-entrepreneurs. The study findings offer important insights into policy and practice by uncovering new dimensions of market development for micro-entrepreneurs in emerging markets.